(3CdajI GHf eGdcs - (3GdWGFj, GdCfOdSj, GdLjGfj, GHf eGdc, LeGd GdOjf, eMeO Hf YHO Gddg Hf eGdc, J (B672 (3g`s
(3ChdgG (B:s
(3bGd eMeO gh GHf eGdc CMeO QHj Gddg NjQ eGdc (B** (3eUdjG Ydi GdfHj GdeUWai hBdg GdeSJcedjf GdTQaG (B** (3hCSJYjf Gddg aj CdajI ebGUO GdfMh HgG eMhjI (B...s
(3BNQgG (B:s
.. (3heG HLeYg YfjJ bO ced fXeG Ydi Ld GdegeGJ GTJed (B** (3CMUj ef GdcGajI GdNdGUI ceG GbJVi ZfG HdG NUGUI (B.. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\233s
(3cTa GdXfhf (B1\ 152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs